Picture Archiving and Communication System Design and Implementation - Samaan, Sama Salam (Nahrain University College of Engineering Journal, 2017)
PACS (Picture archiving and communication system) has been vastly introduced as a reliable alternative to the conventional film- and paper-based healthcare system. It has been in existence for several years and has become an integral part of the infrastructure of radiology and imaging departments across the world. Services provided by PACS establish a platform for the diagnosis of different diseases. PACS serves as a more convenient means of teaching students of radiology, it also reduces transmissions time requirement for referral cases and access time to images and radiological report over the network and improves on the time of patient consultation. In this paper we discuss the construction of (PACS) for hospitals that provides electronic storage, retrieval, manipulation, distribution and presentation of medical images using a popular format named DICOM. This research work implements a PACS model with the incorporation of new features. Its objectives were achieved: converting non DICOM images to DICOM standard and reduced transmission time and storage space requirements of radiological images. The model is implemented using the visual studios.Keywords: ,, , ,